Predictive value of pretreatment albumin‐to‐alkaline phosphatase ratio for overall survival for patients with advanced non‐small cell lung cancer. (21st July 2020) - Zhou, Shaozhang; Jiang, Wei; Wang, Huilin; Wei, Ni; Yu, Qitao
Abstract: Objectives: To investigate the relation between AAPR and OS in patients with advanced non‐small cell lung cancer (NSCLC). Methods: A retrospective cohort study was conducted with 808 patients with advanced NSCLC who were treated in Guangxi Medical University Affiliated Tumor Hospital in China from 5 March 2009 to 31 August 2018. The target‐independent and dependent variables were AAPR measured in patients before anticancer treatment and overall survival (OS), respectively. Covariates involved in this study included age, gender, ECOG status, smoking history, clinical stages, pathological type, driver mutation (EGFR or ALK), metastasis or not (bone, lung, liver, brain, malignant plural effusion, and other organs), number of organ metastasis(≤3, >3), first‐line regiment and number of treatment lines (≤3, >3). Results: The mean age of the selected patients was 58.3 ± 10.9 years and 68.6% were male. We divided patients according to their AAPR into low (AAPR < 0.34, n = 266), medium (AAPR = 0.34‐0.47, n = 259), and high (AAPR > 0.47, n = 283) tertile groups. Medium and high AAPR were associated with a decreased risk of death after fully adjusted Cox proportional hazard model(s) with hazards ratio (HR) 0.77 (95%CI = 0.58‐1.03) and HR 0.59 (95%CI = 0.45‐0.78), respectively ( P for trend <.05). The median OS of low, medium, and high AAPR was 9.3, 11.8, and 16.9 months, respectively ( P value <.0001). No optimal cutoff value of AAPR for prognosing OS was identified by smooth curve fitting. The HR and the 95% confidence intervals of the left and right sides of the inflection point 0.6 as cutoff value were 0.28 (95%CI = 0.14‐0.57) and 0.77 (95%CI = 0.34‐1.73), respectively ( P value = .127). By subgroup analysis, similar results were consistently observed across nearly all the subgroups. Conclusion: Our study implied that pretreatment AAPR can be used as an independent prognostic factor in patients with advanced NSCLC. This ratio should be applied for risk stratification and clinical decision‐making in those patients. Abstract : Using a retrospective cohort study with a large number of patients, this study investigates the relationships between albumin‐to‐alkaline phosphatase ratio as a prognostic factor for patients with advanced non‐small cell lung cancer.